Efektivitas Pengelolaan Anggaran Dana Desa Tahun 2021 Dalam Meningkatkan Pembangunan di Desa Patiluban Hillir, Kecamatan Natal, Kabupaten Mandailing Natal Sumatera Utara - Pratama, Radivan; Junaidi, Junaidi; Ashani, Sholahuddin (Regress: Journal of Economics & Management, 2024)
This article aims to investigate the effectiveness of village fund management in enhancing both physical and non-physical development in Patiluban Hillir Village, Natal District, Mandailing Natal Regency. This research employs a qualitative study design with a qualitative descriptive data approach. The data collection technique employed in this research is purposive sampling, involving 5 individuals designated as research subjects. Data gathering is conducted through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The research findings indicate that: (1) Village fund management in Patiluban Hillir involves a fund allocation of 766 million in 2021, distributed across various sectors such as natural disaster mitigation, empowerment, community welfare, and development. However, the process of fund allocation lacks transparency, as the community is only informed of the total amount of village funds obtained without knowledge of the specific sectors it will be allocated to. Additionally, there is a lack of enthusiasm among the community members, leading to low participation during village deliberations and activities. (2) Development in Patiluban Hillir Village in 2021 prioritizes non-physical aspects, particularly focusing on natural disaster management such as flood and Covid-19. Meanwhile, in non-physical development, the government will undertake community awareness campaigns.